ANALISIS DAYA TARIK WISATA BERDASARKAN 4A (ATTRACTION, ACCESSIBILITY, AMENITIES, DAN ANCILLIARY) DI PURA MANGKUNEGARAN SURAKARTA - Anisah Hamid (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Pura Mangkunegaran is one of the leading cultural tourism destinations in Surakarta that continues to develop through various cultural attractions and creative economy activities. This study aims to analyze the role of Attraction, Accessibility, Amenities, and Ancillary (4A) in increasing tourists' intention to visit Pura Mangkunegaran. The research employed a quantitative approach with data collected through questionnaires distributed to tourists. Data were analyzed using descriptive statistics. The results indicate that all 4A components contribute to increasing tourists' visit intention. Attraction is the most dominant factor, supported by cultural uniqueness, historical value, architectural heritage, and the organization of various cultural attractions and events. Meanwhile, accessibility, amenities, and ancillary services act as supporting factors that enhance tourists' comfort and overall experience. Therefore, the development of cultural tourism attractions should be continuously promoted to maintain the attractiveness and competitiveness of Pura Mangkunegaran as a cultural tourism destination in Surakarta.